2017
DOI: 10.3892/ol.2017.5995
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of novel N(4)-substituted thiosemicarbazones bearing a pyrrole unit as potential anticancer agents

Abstract: Abstract.A series of N(4)-substituted thiosemicarbazones (TSCs) bearing pyrrole unit (1a-1e) were synthesized and fully characterized by elemental analyses, infrared spectra, 1 H nuclear magnetic resonance and single crystal X-ray diffraction. The compounds were assessed as potential chemotherapeutic agents. All newly synthesized compounds were screened for their anticancer activity against lung cancer PC-9, esophageal cancer Eca-109 and gastric cancer SGC-7901 cell lines. The results of MTT, Terminal deoxynuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The four-coordinated Ni(II) ion is in a distorted square planar geometry with the donor sets of two N and two S atoms from two dependent TSC ligands. The length of C-S is 1.736(3) Å, which is much longer than that of 1.691(19) Å in the free molecule [6], showing that the TSC ligand has thiolated and deprotonated. Furthermore, the imine C=N (C8-N2) bond adopted a Z configuration instead of E in the free molecule [6].…”
Section: Commentmentioning
confidence: 79%
See 2 more Smart Citations
“…The four-coordinated Ni(II) ion is in a distorted square planar geometry with the donor sets of two N and two S atoms from two dependent TSC ligands. The length of C-S is 1.736(3) Å, which is much longer than that of 1.691(19) Å in the free molecule [6], showing that the TSC ligand has thiolated and deprotonated. Furthermore, the imine C=N (C8-N2) bond adopted a Z configuration instead of E in the free molecule [6].…”
Section: Commentmentioning
confidence: 79%
“…The length of C-S is 1.736(3) Å, which is much longer than that of 1.691(19) Å in the free molecule [6], showing that the TSC ligand has thiolated and deprotonated. Furthermore, the imine C=N (C8-N2) bond adopted a Z configuration instead of E in the free molecule [6]. In the solid state, intermolecular N-H• • • O hydrogen bonds between the terminal amino N and carboxylate O atoms link molecules into a two-dimensional supermolecular network.…”
Section: Commentmentioning
confidence: 79%
See 1 more Smart Citation
“…Some studies showed that pyrrole unite containing compounds have antitumor activity (Vine et al., 2009), so a series of N (4)‐substituted thiosemicarbazones bearing a pyrrole unit were assessed as potential chemotherapeutic agent (Huang et al., 2010). Zhu et al., (2017) synthesized five compounds and characterized by spectroscopic techniques. The synthesized compounds were assayed for cytotoxicities against SGC −7901 (gastric), PC‐9 (lung), and Eva 109 (esophageal) cancer cell lines.…”
Section: Caspase‐3 Activatorsmentioning
confidence: 99%
“…Significantly, the biological properties of thiosemicarbazone compounds are comparatively higher than that of the other transition metal complexes probably due to the synergic effect among thiosemicarbazone ligands and the presence of central metal ion [6]. Recently, Zhu et al found that potential biological properties of novel N(4)-substituted thiosemicarbazide with pyrrole moiety against PC-9, Eca-109, and SGC-7901 cell lines [7]. Moreover, the substituted thiosemicarbazone at N(4) position did not show any effect on the geometry of the complexes, but it influences the biological activity of the corresponding complexes and shows significant activity.…”
Section: Introductionmentioning
confidence: 99%